2019
DOI: 10.1371/journal.ppat.1007724
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized low-density lipoprotein (oxLDL) supports Mycobacterium tuberculosis survival in macrophages by inducing lysosomal dysfunction

Abstract: Type 2 diabetes mellitus (DM) is a major risk factor for developing tuberculosis (TB). TB-DM comorbidity is expected to pose a serious future health problem due to the alarming rise in global DM incidence. At present, the causal underlying mechanisms linking DM and TB remain unclear. DM is associated with elevated levels of oxidized low-density lipoprotein (oxLDL), a pathologically modified lipoprotein which plays a key role during atherosclerosis development through the formation of lipid-loaded foamy macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 104 publications
1
39
0
Order By: Relevance
“…Together with the evidence associating non-replicating persistence with phenotypic drug tolerance (Gold and Nathan, 2017), this link has underpinned the notion that ILI-containing bacilli, such as those detected in the sputum of TB patients, are "fat and lazy" (Garton et al, 2008) and phenotypically drug tolerant (Turapov et al, 2016). However, in contrast to these studies, Mtb showed no significant growth impairment in necrosis-associated foamy macrophages (NFAMs) (Jaisinghani et al, 2018) and showed even better growth in human macrophages which became foam cells by incubation with oxidized low-density lipoprotein than in resting macrophages (Vrieling et al, 2019), further highlighting differences between the various models.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the evidence associating non-replicating persistence with phenotypic drug tolerance (Gold and Nathan, 2017), this link has underpinned the notion that ILI-containing bacilli, such as those detected in the sputum of TB patients, are "fat and lazy" (Garton et al, 2008) and phenotypically drug tolerant (Turapov et al, 2016). However, in contrast to these studies, Mtb showed no significant growth impairment in necrosis-associated foamy macrophages (NFAMs) (Jaisinghani et al, 2018) and showed even better growth in human macrophages which became foam cells by incubation with oxidized low-density lipoprotein than in resting macrophages (Vrieling et al, 2019), further highlighting differences between the various models.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, the upregulated gene in unstable carotid plaque was enriched in the tuberculous pathways; this result may imply that tuberculosis infection is correlated with plaque instability. The treatment of oxidized low-density lipoprotein inhibits macrophage lysosomes from combining with Mycobacterium tuberculosis , thereby supporting the survival of the microorganism 33 ) . Atherosclerosis may in turn drive the development of tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…These metabolic changes may play a role in the mechanism of the deactivated phenotype since metabolism and macrophage function are highly dependent 36. For instance, it has been shown that T2D promotes an impaired control of M. tuberculosis in human foamy macrophages by inducing lysosomal dysfunction 37. Additionally, previous work has shown that PMs from Ldlr −/− mice fed a Western diet show a deactivated phenotype 23 38.…”
Section: Discussionmentioning
confidence: 99%